Supersymmetric soliton solution in a dimensionally reduced schrödinger-chern-simons model - Sourrouille, Lucas (2011)
We obtain, by dimensional reduction, a (1+1) supersymmetric system introduced in the description of ultracold quantum gases. The correct supercharges are identified and their algebra is constructed. Finally, novel solitonic equations emerge and their solution is constructed for the bosonic case.